Genetic characterization of multidrug-resistant Escherichia coli harboring colistin-resistant gene isolated from food animals in food supply chain - Chopjitt, Peechanika; Boueroy, Parichart; Morita, Masatomo; Iida, Tetsuya; Akeda, Yukihiro; Hamada, Sihigeyuki; Kerdsin, Anusak (Frontiers in Cellular and Infection Microbiology, 2024)
Colistin is widely used for the prophylaxis and treatment of infectious disease in humans and livestock. However, the global food chain may actively promote the dissemination of colistin-resistant bacteria in the world. Mobile colistin-resistant (mcr) genes have spread globally, in both communities and hospitals. This study sought to genomically characterize mcr-mediated colistin resistance in 16 Escherichia coli strains isolated from retail meat samples using whole genome sequencing with short-read and long-read platforms. To assess colistin resistance and the transferability of mcr genes, antimicrobial susceptibility testing and conjugation experiments were conducted. Among the 16 isolates, 11 contained mcr-1, whereas three carried mcr-3 and two contained mcr-1 and mcr-3. All isolates had minimum inhibitory concentration (MIC) for colistin in the range 1–64 μg/mL. Notably, 15 out of the 16 isolates demonstrated successful transfer of mcr genes via conjugation, indicative of their presence on plasmids. In contrast, the KK3 strain did not exhibit such transferability. Replicon types of mcr-1-containing plasmids included IncI2 and IncX4, while IncFIB, IncFII, and IncP1 contained mcr-3. Another single strain carried mcr-1.1 on IncX4 and mcr-3.5 on IncP1. Notably, one isolate contained mcr-1.1 located on a chromosome and carrying mcr-3.1 on the IncFIB plasmid. The chromosomal location of the mcr gene may ensure a steady spread of resistance in the absence of selective pressure. Retail meat products may act as critical reservoirs of plasmid-mediated colistin resistance that has been transmitted to humans.